Alteration of hydrological conditions and spreading processes in vegetated natural flows - Ben Meftah, Mouldi; De Serio, Francesca; Mossa, Michele (Italian journal of engineering geology and environment, 2018)
<span data-sheets-value="{"1":2,"2":"Aquatic vegetation provides a wide range of ecosystem services. The uptake of nutrients and production of oxygen improve water quality. The widespread planting in waterways could strongly contribute to the removal of nitrogen and phosphorous. Seagrasses form the foundation of many food webs and vegetation promotes biodiversity by creating different habitats with spatial heterogeneity in the stream velocity. Marshes and mangroves reduce coastal erosion by damping waves and storm surge, as well riparian vegetation enhances bank stability. Even more in times of a changing climate, which could alter hydrological conditions, the monitoring of vegetation development is a fundamental activity in coastal and river management, to both protect ecological services and control flood or erosion risks. A further key point remains poorly investigated and still deserves a thorough study, that is the effect induced by vegetation or similar obstructions on a discharged effluent assumed as a turbulent jet. The present paper shows how vegetation greatly affects the jet entrainment, reversing it into a detrainment process, the diffusion and advection of the jet solute\rand particles and the jet momentum, demonstrating that it is one of the main cause of the river morphology alteration."}" data-sheets-userformat="{"2":13057,"3":{"1":0},"11":0,"12":0,"15":"Arial","16":10}">Aquatic vegetation provides a wide range of ecosystem services. The uptake of nutrients and production of oxygen improve water quality. The widespread planting in waterways could strongly contribute to the removal of nitrogen and phosphorous. Seagrasses form the foundation of many food webs and vegetation promotes biodiversity by creating different habitats with spatial heterogeneity in the stream velocity. Marshes and mangroves reduce coastal erosion by damping waves and storm surge, as well riparian vegetation enhances bank stability. Even more in times of a changing climate, which could alter hydrological conditions, the monitoring of vegetation development is a fundamental activity in coastal and river management, to both protect ecological services and control flood or erosion risks. A further key point remains poorly investigated and still deserves a thorough study, that is the effect induced by vegetation or similar obstructions on a discharged effluent assumed as a turbulent jet. The present paper shows how vegetation greatly affects the jet entrainment, reversing it into a detrainment process, the diffusion and advection of the jet solute and particles and the jet momentum, demonstrating that it is one of the main cause of the river morphology alteration.